Kamchatka Berry ( Lonicera caerulea L.) Pomace Bioferment as an Innovative Cosmetic Raw Material - Weronika Majchrzak; Krzysztof Śmigielski; Ilona Motyl; Joanna Oracz; Karina Skura; Sara Motyl (Applied Sciences, 2024)
Kamchatka berries ( Lonicera caerulea L.) are known for their high content of phenolic compounds or vitamins, which is reflected in their antibacterial, detoxifying and anti-inflammatory properties. They are used in the production of jams, juices, wines and as natural dye. A bioferment was prepared from the pomace of the Kamchatka berry varieties Aurora and Indigo Gem and the strains Saccharomyces cerevisiae and Lacticaseibacillus paracasei , which was used to prepare a cosmetic preparation with a concentration of 5% in accordance with the guidelines of the COSMOS certification body. We conducted physico-chemical and organoleptic analyses and bioactive profile characterisation (UHPLC-DAD and UHPLC-ESI-MS/MS). The results showed that the presence of caffeic acid (4.47 ± 0.07 mg/100 g) was detected after fermentation of Kamchatka berry pomace. In addition, vitamin C content increased by 141% after fermentation. The results of stability tests showed that in the process of physico-chemical analysis of the cosmetic preparation with bioferment of Kamchatka berry pomace, the pH should oscillate in the range of 4.38–4.76 ± 0.01. Stability tests showed that the cosmetic should be protected from high temperatures and UV radiation and proved that the product is stable under changing conditions, resulting in lower transport and storage costs.